Translation and validation to brazilian portuguese of Self Assessment of Occupational Functioning Scale: DOI: 10.15343/0104-7809.2010230237 - Tedesco, Solange Aparecida (2010)
The article presents the translation to the Portuguese language, the transcultural adaptation and the validation of SelfAssessment of Occupational Functioning Scale for using with the Brazilian population. We did the stages of semantic and conceptualequivalence both in translation and in transcultural adaptation procedures. The adapted scale is a practical instrument for occupationaltherapists with reproductibility for the 23 (twenty three) component and the 7 (seven) areas. The scale was considered significant andhighly satisfactory, suggesting the indication of the use of this suitable version.